Factors Predicting the Length of Hospital Stay in Infants with Bronchitis at Bethesda Hospital, Yogyakarta - Puspita, Nita; Purnajati, Oscar Gilang; Nugroho, Daniel Chriswinanto Adityo; Martelina, Yiska (Jurnal Respirasi, 2025)
Introduction: Bronchitis is a primary cause of hospitalization in toddlers due to acute respiratory infections (ARI). Hospitalization is particularly necessary in this age group because their immature immune systems render them highly vulnerable to complications such as respiratory failure and secondary infections. Elevated, inflammatory responses reflected by increased leukocyte counts necessitate close clinical monitoring and intensive care to prevent deterioration. Therefore, inpatient care plays a crucial role in ensuring the clinical stability and effective recovery of toddlers with bronchitis. This study analyzed the predictive factors influencing the length of hospital stay in toddlers with bronchitis treated at Bethesda Hospital, Yogyakarta. Methods: This study employed a quantitative approach using an observational analytic method with a cross-sectional design. Data were collected from 90 medical records of 105 hospitalized toddlers aged 1-59 months due to bronchitis in 2023. Age, sex, nutritional status, hemoglobin (Hb) levels, and leukocyte count were the analyzed variables. The data were analyzed using Chi-square and logistic regression. Results: Age and leukocyte count were significantly associated with the length of hospital stay (p<0.05). Younger toddlers were more likely to experience prolonged hospitalization (adjusted odds ratio/OR=0.242), while an increased leukocyte count (leukocytosis) elevated the risk of a longer hospital stay (adjusted OR=4.137). Other variables, including sex, nutritional status, and Hb levels, did not significantly influence prolonged hospitalization. Conclusion: Age and leukocyte count were predictive factors for the length of hospital stay in toddlers with bronchitis at Bethesda Hospital, Yogyakarta, in 2023.